KONFLIK BATIN TOKOH MARK: EKSPLORASI DIMENSI PSIKOSOMATIS DENGAN PENDEKATAN FREUDIAN DALAM DINAMIKA KELUARGA M (BLOOMINGTON RESIDENT) - M. Hikmal Yazid (Jurnal Bahasa Indonesia Prima (BIP), 2024)
This study aims to conduct a Freudian psychosomatic analysis of the moral struggle of Mark's character in the short story "Keluarga M" by Budi Darma. The research object of the short story focuses on Mark's character development and inner conflict involving the interaction between Freudian basic drives, moral values, and social norms. Freudian psychosomatic theory is used as a conceptual framework. This study identifies and analyzes the conflict between the id, ego, and superego in Mark's psyche to understand the tension between basic drives, such as personal desire and recklessness, and the formation of social norms. Character complexity. This study hypothesizes that significant inner conflicts in Mark's moral struggle will be revealed through Freudian psychosomatic analysis. Based on the assumption that the interaction between these psychological components affects the character's behavior and emotions, this research seeks to provide in-depth insight into the complexity of humans in facing moral dilemmas through literary media. The results of this research are expected to provide a deeper understanding of Mark's character and how his moral struggle reflects human psychological dynamics.